2012
DOI: 10.1002/tox.21833
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 system expression and DNA adduct formation in the liver of Zacco platypus following waterborne Benzo(a)pyrene exposure: implications for biomarker determination

Abstract: Benzo(a)pyrene (BaP) is a polycyclic aromatic hydrocarbon that causes mutations and tumor formation. Zacco platypus is a sentinel species that is suitable for monitoring aquatic environments. We studied cytochrome P450 system (CYP system) expression and DNA adduct formation in the liver of Z. platypus following waterborne exposure to BaP. The results showed both dose and time dependency. The significant induction levels of CYP system mRNA and protein reached maximums at 2 days and 14 days, respectively, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The regulation of CYP enzyme activity may play a central role in the adaptation of aquatic and/or marine animals to environmental pollutants. In Zacco platypus , Lee et al (2014) reported significant inductions of CYP system mRNA and protein, as well as increases in the hepatosomatic index, which reached maximum levels at 2, 14 and 4 days, respectively, during a 14-day B a P exposure; they suggested that a combination of the CYP system mRNA and protein expression levels, and the hepatosomatic index, would provide a useful biomarker in risk assessments of waterborne B a P exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of CYP enzyme activity may play a central role in the adaptation of aquatic and/or marine animals to environmental pollutants. In Zacco platypus , Lee et al (2014) reported significant inductions of CYP system mRNA and protein, as well as increases in the hepatosomatic index, which reached maximum levels at 2, 14 and 4 days, respectively, during a 14-day B a P exposure; they suggested that a combination of the CYP system mRNA and protein expression levels, and the hepatosomatic index, would provide a useful biomarker in risk assessments of waterborne B a P exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, BaP induced both CYP1A mRNA and protein expressions in liver and gills of four well known model species (freshwater minnow Zacco platypus, zebrafish Danio rerio, Japanese medaka Oryzias latipes, and common carp Cyprinus carpio) (Lee et al, 2015). Moreover, a positive correlation has been observed between CYP1A protein levels and DNA adduct formation in the teleost fish Z. platypus upon exposure to BaP (Lee et al, 2012). In BaP-exposed killifish (Fundulus grandis and F. similus), a dose-dependent increase in the formation of DNA adducts has been reported, along with significant modulation of CYP1A genes (Willett et al, 1995).…”
Section: Case Study 1: Benzo(a)pyrene-induced Cancer In Fishmentioning
confidence: 94%
“…2). The MIE of BaP exposure is the binding of BaP to the AhR (Hahn, 2002;Lin et al, 2003b;Wang et al, 2010), leading to AhR activation and CYP1A expression in teleost fish (Haasch et al, 1993;Levine and Oris, 1999;Hahn, 2002;Bo et al, 2010;Wang et al, 2010;Lee et al, 2012). In the red sea bream Pagrus major, expression of Pm-CYP1A1 and Pm-AhR2 is induced simultaneously in a time-dependent and dose-dependent manner (Bo et al, 2010).…”
Section: Case Study 1: Benzo(a)pyrene-induced Cancer In Fishmentioning
confidence: 95%
“…Oryzias latipes has been used widely as an experimental fish for monitoring pollutants for over a century [2]. Fish liver is a major detoxification organ and the gills and intestine are useful monitor organs that reflect the health of aquatic organisms and have been used as target organs in aquatic toxicity studies [35]. …”
Section: Introductionmentioning
confidence: 99%